Collision avoidance for unmanned surface vehicle in busy waterways based on improved DDPG and IMMKF - Te Lian; Qijun Liu; Defeng Wu; Yuqin Li; Chunxin Tian (Ocean Engineering, 2026)

Optimizing initial biomass to enhance microplastic sequestration via density-driven bio-flocculation in microalgal systems - Xiaoxue Mei; Jiawei Wang; Xueying Zhao; Yilu Liang; Baiyun Lu; Yawen Fan; Defeng Xing; Nanqi Ren; Yan Liu (Bioresource Technology, 2026)

Flotation mechanism of an amide-based fatty acid collector for quartz ore: A gene-matching perspective - Wenda Guo; Baida Chen; Zhenyue Zhang; Sicheng Li; Han Zhang; Heng Zhang; Hanjun Wu; Defeng Liu (Minerals Engineering, 2026)

Development and validation of CFDT code for fission product release analysis of spherical and cylindrical TRISO-based fuel element in HTGRs - Liying Zhang; Defeng Yang; Xiaoxia Wang; Aijun Mi; Guoming Liu; Liangzhi Cao; Jinkai Liu; Shiyu Liu; Pengpei Xie; Qingmin Zhang (Annals of Nuclear Energy, 2026)

Alfalfa polysaccharides-driven Kineothrix alysoides alleviates deoxynivalenol-induced intestinal injury by regulating macrophage polarization - Shouren Li; Zhaoyang Li; Congbin Chen; Mengqi Liu; Yalei Cui; Xiaoyan Zhu; Zhichang Wang; Hao Sun; Defeng Li; Boshuai Liu; Yinghua Shi (Journal of Hazardous Materials, 2026)

Numerical Simulation of Large Deformation Movement Process of Underwater Slope Subjected to Seismic Loads: A Case Study from the St. Niklausen Landslide - Mingzhe Wei; Zhongde Gu; Ze Rong; Yang Liu; Yang Lu; Defeng Zheng; Tingkai Nian (Journal of Marine Science and Engineering, 2026)
Large deformation runout is a key factor in assessing the hazards posed by underwater landslides. However, conventional kinematic analyses often neglect both the progressive degradation of slope materials and the hydrodynamic response accompanying the interaction between the moving mass and the overlying water. Taking the well-documented St. Niklausen underwater landslide as a representative case, this study employs a coupled Eulerian–Lagrangian (CEL) model to investigate the earthquake-triggered initiation, large deformation movement, and hydrodynamic response of the landslide. A Python 2.7.15-based stress mapping method is developed to establish an accurate initial geostatic stress field for the irregular slope profile. The numerical model reproduces the principal stages of landslide initiation, runout, and deposition. The results reveal a progressive retrogressive failure mechanism in which successive sliding masses interact through a high-strength compression zone. The rear sliding mass continuously transfers compressive work to the frontal mass, thereby maintaining its downslope movement and indirectly promoting basal erosion to a maximum depth of approximately 6.2 m. In addition, rapid landslide motion generates pronounced vortical flow in the overlying water. These flow structures reflect the hydrodynamic response induced by landslide motion, although their net influence on basal resistance and final runout cannot be isolated from the present coupled simulation. These findings clarify the internal mechanical evolution of underwater landslide movement and characterize the accompanying hydrodynamic response, providing a methodological basis for assessing landslide mobility and related underwater hazards.

Identification of Gibberellin-mediated Key Genes for Salt Tolerance in Alfalfa Based on Transcriptomic Analysis - Guomin Li; Xiangling Ren; Wenxuan Zhu; Yingao Li; Zirui Liu; Xi Wang; Defeng Li; Yinghua Shi; Xiaoyan Zhu; Chengzhang Wang; Hao Sun (Plant Molecular Biology Reporter, 2026)

Microplastic accumulation in paired human breast tumor and para-tumor tissues and exploratory clinical associations - Limin Jia; Yanni Song; Yufeng Guo; Fuyu Yang; Qiyan Guan; Weihan Zhang; Yang Liu; Defeng Xing; Yanhong Lv (Journal of Hazardous Materials, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Experimental and numerical study on real-time early warning of secondary collapse in semi-ruined RC frame structures under aftershocks - Defeng Xu; Feifei Sun; Yue Liu; Jixin Wen (Bulletin of Earthquake Engineering, 2026)

Reutilization of digestate (residue and liquid) in the anaerobic digestion of sole corn stover: biochar preparation, methane performance and microbial responses - Haipeng Wang; Hao Sun; Sheng-Nan Zhuo; Jianrui Li; Zetang Chai; Jingwen Jia; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Environmental Management, 2026)

Electrically enhanced microalgae-bacteria systems for wastewater treatment under low-temperature conditions - Qitong Cai; Zhengpeng Wang; Xinyu Li; Yan Liu; Nanqi Ren; Defeng Xing; Xiaoxue Mei; Yawen Fan (Bioresource Technology, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Synthesis and mechanistic insights of α-chlorinated lauric acid as a high-efficiency collector for apatite flotation - Wenda Guo; Heng Zhang; Zhenyue Zhang; Haolong Lu; Defeng Liu; Hanjun Wu (Minerals Engineering, 2026)

Bioaugmentation of strain Bacillus sp. hex-HIT36 towards industrial wastewater 1-Hexadecene removal in biological aerated filter reactors - Lei Yang; Yijie Liu; Yuxin Pan; Xue-Ting Wang; Wei Wang; Xijun Xu; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

Sesquiterpenoids from Euphorbia esula L. - Defeng Yan; Miaomiao Zhang; Dan Tang; Yuqing Song; Liu Liu; Haiqing Zhao; Nurmirza Begmatov; Orzimat Turdimatovich Turginov; Bo Zhao; Hequn Yang; Guoan Zou (Phytochemistry, 2026)

Experimental investigation on the high-speed suspension hexamaran in head waves - Xin Liu; Jinglei Yang; Defeng Wu; Haibin Wang; Jingheng Wu; Liang Hou; Lei Du; Qian Wan (Ocean Engineering, 2026)

Charge-specific impacts of polystyrene nanoplastics on acidogenesis and biofilm adaptation in Ethanoligenens harbinense - Jing Wang; Weimin Zhu; Xingze Zhang; Sitong Liu; Jun Ma; Defeng Xing (Bioresource Technology, 2026)

Identification of a NEK7-related pyroptosis gene signature against pancreatic cancer and evaluation of its potential in tumor microenvironment remodeling via regulating inflammasome complex - Jia Liu; Zilong Yan; Tongning Zhong; Jianhua Qu; Defeng Lei; Jinglin Lai; Citing Zhang; Zhengquan Lai; Weipeng Ai; Xueqing Liu (Functional & Integrative Genomics, 2025)

Effect of myofibrillar protein structure changes mediated by NaCl on the binding capacity of volatile compounds in Cantonese sausage - Yuanhong Zhang; Defeng Zeng; Shihong Cai; Qiaoyu Liu; Weizheng Sun; Xin Hu; Hui Peng; Hao Dong; Xiaofang Zeng (Food Chemistry, 2025)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Self-regulating adaptability of biofilm microbiomes enhances manganese and ammonia removal in microbial electrochemical filters under dioxane exposure - Sitong Liu; Kun Feng; Dawei Zhang; Yang Liu; Jing Wang; Baiyun Lu; Defeng Xing (Journal of Hazardous Materials, 2025)

Krϋppel-like factor 12a and 12b inhibit Cyvirus cyprinidallo3 replication by repressing viral ORF8 promoter activity - Xinyue Hu; Yingying Li; Yingying Wang; Defeng Zhang; Donghai Liu; Qing Wang; Shucheng Zheng (Fish & Shellfish Immunology, 2025)

Reassessing systemic blind spots in modern water disinfection paradigms - Yang Liu; Jialiang Gu; Kun Feng; Yangyang Zhang; Zheng Zhong; Sitong Liu; Defeng Xing (Journal of Hazardous Materials, 2025)

Direct ammonia oxidation colony-driven DAAO process: construction strategy and optimization of denitrification efficacy - Yuwei Mi; Dingqiu Wei; Shuangjiang Liu; Defeng Li; Han Chen; Yijie Zheng; Mingming Chen; Dongru Qiu; Renbing Bao; Jian Xu; Zhiquan Hu (Chemical Engineering Journal, 2025)

Migration law of micro-fine particles and enhancement of leaching process in weathered crust elution-deposited rare earth ores - Defeng Liu; Shijia Zhang; Zhenyue Zhang; Wenda Guo; Ruan Chi (Minerals Engineering, 2025)

FeCN/MXene as novel heterogeneous electro-Fenton catalysts for the degradation of sulfathiazole: Performance and mechanism investigation - Huilai Liu; Zhihao Li; Defeng Kong; Xing Chen (Journal of Environmental Sciences, 2025)

AMP1-1 derived from Atractylodes macrocephala Koidz prevents bone aging triggered by lead and cadmium - Jinpeng Wang; Yu Jiang; Xiaoyu Hou; Tahir Raza; Yiping He; Xinyue Liu; Defeng Xing; Lijun Wei (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Precise baseline determination for the four-satellite InSAR constellation HT-01 with ambiguity resolution constraints - Dachen Peng; Shibo Guo; Defeng Gu; Kai Shao; Houzhe Zhang; Ruiyun Yang; Jufeng Lu; Jiangkai Liu; Haoseng Wang; LiuPeng Huang (Advances in Space Research, 2025)

Enhancement of mass transfer process in column leaching by graded combination of coarse–medium–fine (C–M–F) particle packing: Application to heap leaching of ion-adsorption type rare earth ore with mixed (NH4)2SO4 and NH4Cl solution - Defeng Liu; Yuzhi Wang; Zhenyue Zhang; Ruan Chi (Hydrometallurgy, 2025)

Experimental study on shear performance of prefabricated HSS-UHPC composite beam with perfobond strip connectors - Shaohua He; Defeng Zhou; Baisheng Bai; Changxi Liu; You Dong (Engineering Structures, 2025)

Applying machine learning and genetic algorithms accelerated for optimizing ethanol production - Xu Yang; Nianhua Chen; Hui Yu; Xinyue Liu; Yujie Feng; Defeng Xing; Yushi Tian (Science of The Total Environment, 2024)

Experimental study of a high-speed suspension hexamaran in calm water - Xin Liu; Jinglei Yang; Defeng Wu; Liang Hou; Lei Du; Qian Wan (Ocean Engineering, 2024)

Process exploration of domestication, start-up and rapid recovery strategies for anaerobic digestion of sole corn stover: Methane production efficiency and dominant microbial responses - Haipeng Wang; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Cleaner Production, 2024)

Integrated transcriptome and metabolome profiles reveal the regulatory molecular mechanisms of meat quality in pasture-fed goose - Qasim Ali; Boshuai Liu; Shaokai La; Umar Farooq; Yao Han; Mengqi Liu; Yan Zhang; Defeng Li; Zhichang Wang; Hao Sun; Yalei Cui; Sen Ma; et al. (Food Bioscience, 2024)

Fluorocarbon polymers mediated contact-electro-catalysis activating peroxymonosulfate for emerging pollutants degradation: The key role of fluorine density in electron transfer - Dongmei Ma; Wei Li; Jin Zhang; Kuanchang He; Changyong Zhang; Gang Wang; Xiaodong Xin; Qian Liu; Faliang Cheng; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2024)

Bonding characteristics between existing concrete substrate and high ductility geopolymer overlays under direct shear loading - Shan Li; Wentao Ma; Defeng Chen; Yiyan Lu; Zhenzhen Liu (Engineering Structures, 2024)

Chitin nanocrystals-stabilized emulsion as template for fabricating injectable suspension containing polylactide hollow microspheres - Sumin Yu; Guangni Peng; Jiali Jiao; Peng Liu; Huajun Li; Juqun Xi; Defeng Wu (Carbohydrate Polymers, 2024)

Termite mounds affect soil aggregate stability and aggregate-associated phosphorus forms in a tropical rubber plantation - Fangmei Lin; Yanqiang Jin; Chenggang Liu; Yan Ren; Chuan Jiang; Defeng Feng; Jianwei Tang (Plant and Soil, 2024)

Sequential recovery of protein and ammonium from waste sludge and functional metabolism in a combined process of nutrient recovery electro-fermentation (NREF) - Jiayu Gu; Huihui Zhou; Jing Wang; Kun Feng; Guojun Xie; Bingfeng Liu; Defeng Xing (Resources, Conservation and Recycling, 2024)

An algorithm of dynamic temporal constraints for the mission series in deep space detectors - Yuheng Qi; Yuan Liu; Defeng Gu; Jubo Zhu (Advances in Space Research, 2024)

Baicalin attenuates lipopolysaccharide-induced intestinal inflammatory injury via suppressing PARP1-mediated NF-κB and NLRP3 signalling pathway - Qirong Lu; Nan Wang; Defeng Wen; Pu Guo; Yu Liu; Shulin Fu; Chun Ye; Zhongyuan Wu; Yinsheng Qiu (Toxicon, 2024)

Recycling different crystal forms of MnO2 from spent Li-ion batteries cathodes for SDZ degradation - Xinxin Lv; Fang Deng; Huilai Liu; Yu Zhang; Qingjun Liu; Yueqing Liang; Defeng Kong; Mukhtar Ahmad; Xing Chen (Journal of Environmental Chemical Engineering, 2024)

Effects of polyethylene terephthalate microplastics on cell growth, intracellular products and oxidative stress of Scenedesmus sp. - Jiahui Jiang; Xiaoyu Cai; Hongyu Ren; Guangli Cao; Jia Meng; Defeng Xing; Jes Vollertsen; Bingfeng Liu (Chemosphere, 2024)

Integrating network pharmacology and experimental validation to explore the mechanisms of luteolin in alleviating fumonisin B1–induced intestinal inflammatory injury - Defeng Wen; Wantong Han; Quan Chen; Guanhui Qi; Mengling Gao; Pu Guo; Yu Liu; Zhongyuan Wu; Shulin Fu; Qirong Lu; Yinsheng Qiu (Toxicon, 2024)

Preparation of PCL/lecithin/bacteriocin CAMT6 antimicrobial and antioxidant nanofiber films using emulsion electrospinning: Characteristics and application in chilled salmon preservation - Qibin Li; Weiqi Liang; Linao Lv; Zhijia Fang; Defeng Xu; Jianmeng Liao; Ying Liu (Food Research International, 2024)

The Bacillus velezensis CYS06 Strain Exhibits Promising Applications in Fighting Grass Carp Bacterial Diseases - Lijuan Liu; Dongdong Jiang; Yan Ren; Cunbin Shi; Yajun Wang; Jiyuan Yin; Qing Wang; Defeng Zhang (Fishes, 2023)
Aeromonas septicemia and columnaris disease are major bacterial diseases in grass carp; however, the drugs currently used to control these diseases pose environmental and health risks. This study aimed to screen for a probiotic Bacillus strain with antagonistic activity to prevent and control bacterial diseases in grass carp and to evaluate the antimicrobial activities, biosafety, and biocontrol effects of this strain. A Bacillus strain with antagonistic activity against Aeromonas hydrophila, obtained from grass carp intestines, was screened, and the isolate CYS06 was identified by analyzing the 16S rRNA and gyrA gene sequences. The antimicrobial spectrum of the strain CYS06 was determined, and the activities of amylase, cellulase, protease, and lipase of the strain CYS06 were determined. The whole genome of the strain CYS06 was sequenced using the nanopore sequencing technology platform, followed by the analysis of the antagonistic substance synthesis gene clusters and CAZy enzyme gene families. The biosafety of the strain CYS06 was evaluated via intraperitoneal injection into healthy grass carp. After the strain CYS06 was fed to the grass carp, its biological control effect on this fish was evaluated through artificial infection experiments. The strain CYS06 was identified as Bacillus velezensis, based on molecular identification, which shows broad antimicrobial activity against various fish pathogens. The strain CYS06 secretes amylase, cellulase, protease, and lipase. The genome size of the strain CYS06 is 3,914,159 bp, and it contains eight antagonistic substance synthesis gene clusters and many CAZy enzymes. The strain CYS06 exhibits high biological safety for grass carp, based on the challenge test. Feeding grass carp with the strain CYS06 for 4 weeks significantly enhanced the resistance of the fish to A. hydrophila. Strain CYS06 could inhibit the growth of Flavobacterium columnare under co-culture and reduce the amount of F. columnare adherence on the gills of grass carp, indicating that CYS06 has good potential for the prevention and control of columnaris disease. In conclusion, we isolated an antagonistic probiotic strain, CYS06, which exhibits a biological control effect on septicemia and columnaris disease caused by Aeromonas spp. and F. columnare in grass carp, respectively. This strain contains many antagonistic substance synthesis-related gene clusters and holds the potential to degrade various types of carbohydrates. As a biological control agent, the strain CYS06 exhibits significant potential for the prevention and control of bacterial diseases in grass carp.

Land use change alters carbon and nitrogen dynamics mediated by fungal functional guilds within soil aggregates - Chenggang Liu; Yanqiang Jin; Fangmei Lin; Chuan Jiang; Xiaoling Zeng; Defeng Feng; Fuzhao Huang; Jianwei Tang (Science of The Total Environment, 2023)

Understory vegetation management regulates soil carbon and nitrogen storage in rubber plantations - Yan Ren; Fangmei Lin; Chuan Jiang; Jianwei Tang; Zhaofei Fan; Defeng Feng; Xiaoling Zeng; Yanqiang Jin; Chenggang Liu; Olusanya Abiodun Olatunji (Nutrient Cycling in Agroecosystems, 2023)

Hexavalent chromium disrupts the skin barrier by targeting ROS-mediated mitochondrial pathway apoptosis in keratinocytes - Cheng Wang; Hongqi Shang; Shuyu Zhang; Xiangkun Wang; Defeng Liu; Mingyue Shen; Ning Li; Yunxuan Jiang; Kai Wei; Ruiliang Zhu (Chemico-Biological Interactions, 2023)

Pathogenicity of duck circovirus and fowl adenovirus serotype 4 co-infection in Cherry Valley ducks - Mingyue Shen; Panpan Gao; Cheng Wang; Ning Li; Shuyu Zhang; Yunxuan Jiang; Defeng Liu; Baoyu Jia; Li Xu; Bohan Huang; Ruiliang Zhu; Kai Wei (Veterinary Microbiology, 2023)

Biochar prepared from human feces (HFBC) as a promoter in biohydrogen production using simulated feces as substrate - Pian-Pian Xu; Kai Sun; Jian Du; Guojun Xie; Defeng Xing; Bing-Feng Liu (Chemical Engineering Journal, 2023)

Metagenomic reveals the methanogenesis metabolic mechanism of high-solids anaerobic digestion of human feces under gradient domestication - Haipeng Wang; Hao Sun; Hongyu Ren; Guangli Cao; Guojun Xie; Defeng Xing; Nanqi Ren; Bingfeng Liu (Chemical Engineering Journal, 2023)

Thermophilic dark fermentation fast start-up of hydrogen production with substrate concentration regulation and moderate pretreatment inoculum - Tianming Yin; Wei Wang; Shengnan Zhuo; Guangli Cao; Hongyu Ren; Jianrui Li; Defeng Xing; Guojun Xie; Bingfeng Liu (Fuel, 2023)

A methodology to predict the run-out distance of submarine landslides - Xingsen Guo; Thorsten Stoesser; Defeng Zheng; Qianyu Luo; Xiaolei Liu; Tingkai Nian (Computers and Geotechnics, 2023)

Long Non-coding RNA LOXL1-AS1 Facilitates Colorectal Cancer Progression via Regulating miR-1224-5p/miR-761/HK2 Axis - Tao Guo; Shihao Peng; Defeng Liu; Yangyang Li (Biochemical Genetics, 2022)

MSINGB: A Novel Computational Method Based on NGBoost for Identifying Microsatellite Instability Status from Tumor Mutation Annotation Data - Jinxiang Chen; Miao Wang; Defeng Zhao; Fuyi Li; Hao Wu; Quanzhong Liu; Shuqin Li (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Chain pillar optimization at a longwall coal mine based on field monitoring results and numerical model analysis - Qingwen Shi; Gang Xu; Defeng Wang; Zhengjie Li; Wangrong Liu; Xiao Wang (Arabian Journal of Geosciences, 2021)

Study on the effect of axial and hydraulic pressure coupling on the creep behaviors of sandstone under multi-loading - Defeng Liu; Wenxin Yan; Su Yan; Qinrong Kang (Bulletin of Engineering Geology and the Environment, 2021)

Streptococcus shenyangsis sp. nov., a New Species Isolated from the Oropharynx of a Healthy Child from Shenyang China - Defeng Liu; Chunling Xiao; Xinming Li; Ye Sun; He Qi; Yang Zou (Current Microbiology, 2021)

Description and genomic characterization of Streptococcus symci sp. nov., isolated from a child’s oropharynx - He Qi; Defeng Liu; Yang Zou; Nan Wang; Han Tian; Chunling Xiao (Antonie van Leeuwenhoek, 2021)
Using the culturomics approach, we isolated a new Streptococcus species, strain C17 T , from the oropharynx mucosa sample of a healthy 5-year-old child living in Shenyang, China. We studied the phenotypic, phylogenetic, and genomic characteristics of strain C17 T , which was identified as a Gram-positive, coccus-shaped, non-motile, aerobic, catalase-negative bacteria. Its growth temperatures ranged from 20 to 42 °C, with optimal growth at 37 °C. Acid production could be inhibited by two sugars, trehalose and raffinose. In C17 T , the reactions for enzyme lipase (C14) were confirmed to be negative, whereas those for alkaline phosphatase, α-glucosidase, and hippuric acid hydrolysis were positive. The C17 T genome contained 2,189,419 base pairs (bp), with an average G+C content of 39.95%, encoding 2092 genes in total. The 16S ribosomal RNA sequence showed 99.8% similarity with the newly identified Streptococcus pseudopneumoniae ATCC BAA-960 T . The main fatty acid components in C17 T were C16:0, C18:1 w7c, C18:0, and C18:1 w9c, all of which can be found in other species of the Streptococcus genus. Strain C17 T showed high susceptibility to clindamycin, linezolid, vancomycin, chloramphenicol, and cefepime, and moderate susceptibility to erythromycin. The obtained dDDH value between strain C17 T and the closest species was 52.9%. In addition, the whole genome sequence of strain C17 T had an 82.21–93.40% average nucleotide identity (ANI) with those strains of closely related Streptococcus species, indicating that the strain C17 T was unique among all Streptococcus species. Based on these characteristics, we determine that C17 T is a novel species, named Streptococcus symci sp. nov. (= GDMCC 1.1633 = JCM 33582).

Complete Genome of Bacillus velezensis CMT-6 and Comparative Genome Analysis Reveals Lipopeptide Diversity - Qi Deng; Rundong Wang; Dongfang Sun; Lijun Sun; Yaling Wang; Yuehua Pu; Zhijia Fang; Defeng Xu; Ying Liu; Riying Ye; Sanjun Yin; Sisi Xie; et al. (Biochemical Genetics, 2020)

Oleic Acid Alleviates Cadmium-Induced Oxidative Damage in Rat by Its Radicals Scavenging Activity - Jingwen Wang; Yuanyuan Zhang; Zhijia Fang; Lijun Sun; Yaling Wang; Ying Liu; Defeng Xu; Fanghong Nie; Ravi Gooneratne (Biological Trace Element Research, 2019)

Effects of sludge lysate for Cr(VI) bioreduction and analysis of bioaugmentation mechanism of sludge humic acid - Hongling Chen; Ruofei Jin; Guangfei Liu; Tian Tian; Chen Gu; Jiti Zhou; Defeng Xing (Environmental Science and Pollution Research, 2019)

Capsular polysaccharide of Streptococcus agalactiae is an essential virulence factor for infection in Nile tilapia ( Oreochromis niloticus Linn.) - Defeng Zhang; Xiaoli Ke; Zhigang Liu; Jianmeng Cao; Youlu Su; Maixin Lu; Fengying Gao; Miao Wang; Mengmeng Yi; Fengling Qin (Journal of Fish Diseases, 2019)
Streptococcus agalactiae (Group B Streptococcus , GBS) is associated with diverse diseases in aquatic animals. The capsule polysaccharide (CPS) encoded by the cps gene cluster is the major virulence factor of S. agalactiae ; however, limited information is available regarding the pathogenic role of the CPS of serotype Ia piscine GBS strains in fish. Here, a non‐encapsulated mutant (Δ cps ) was constructed by insertional mutagenesis of the cps gene cluster. Mutant pathogenicity was evaluated in vitro based on the killing of whole blood from tilapia, in vivo infections, measuring mutant survival in tilapia spleen tissues and pathological analysis. Compared to wild‐type (WT) GBS strain, the Δ cps mutant had lower resistance to fresh tilapia whole blood in vitro ( p 0.01), and more easily cleared in tilapia spleen tissue, and was highly attenuated in tilapia and zebrafish. Additionally, compared to the Δ cps mutant, numerous GBS strains and severe tissue necrosis were observed in the tilapia spleen tissue infected with WT strains. These results indicated that the CPS is essential for GBS pathogenicity and may serve as a target for attenuation in vaccine development. Gaining a better understanding of the role, the GBS pathogenicity in fish will provide insight into related pathogenesis and host–pathogen interactions.

Mechanical behavior of Benxi Formation limestone under triaxial compression: a new post-peak constitutive model and experimental validation - Defeng Liu; Changwu Liu; Yaming Kang; Bingbing Guo; Yuan Jiang (Bulletin of Engineering Geology and the Environment, 2018)

Regulation of Thermostable Direct Hemolysin and Biofilm Formation of Vibrio parahaemolyticus by Quorum-Sensing Genes luxM and luxS - Muhan Guo; Zhijia Fang; Lijun Sun; Dongfang Sun; Yaling Wang; Can Li; Rundong Wang; Yang Liu; Hanqiao Hu; Ying Liu; Defeng Xu; Ravi Gooneratne (Current Microbiology, 2018)

Streptococcus agalactiae from tilapia (Oreochromis sp.) transmitted to a new host, bighead carp (Aristichthys nobilis), in China - Defeng Zhang; Xiaoli Ke; Lihui Liu; Maixin Lu; Cunbin Shi; Zhigang Liu (Aquaculture International, 2018)

Reduced antigen presentation capability and modified inflammatory/immunosuppressive cytokine expression of induced monocyte-derived dendritic cells from peripheral blood of piglets infected with porcine circovirus type 2 - Ning Yang; Jiandong Li; Qian Yang; Jinzeng Qiao; Defeng Cui; Fenghua Liu; Huanrong Li; Shuanghai Zhou (Archives of Virology, 2018)

Modeling the effects of different conditions on the inhibitory activity of antimicrobial lipopeptide (AMPNT-6) against Staphylococcus aureus growth and enterotoxin production in shrimp meat - Ning Zhang; Yuehua Pu; Lijun Sun; Yaling Wang; Qi Deng; Defeng Xu; Ying Liu; Malik Hussain; Ravi Gooneratne (Aquaculture International, 2017)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Differential expression of the Toll-like receptor pathway and related genes of chicken bursa after experimental infection with infectious bursa disease virus - Xinfeng Guo; Liqiong Wang; Defeng Cui; Wenke Ruan; Fenghua Liu; Huanrong Li (Archives of Virology, 2012)

Dietary salt modulates the sodium chloride cotransporter expression likely through an aldosterone-mediated WNK4-ERK1/2 signaling pathway - Lingyun Lai; Xiuyan Feng; Defeng Liu; Jing Chen; Yiqian Zhang; Bowen Niu; Yong Gu; Hui Cai (Pflügers Archiv - European Journal of Physiology, 2012)